Environmental enrichment improves hypomyelination, synaptic alterations, and memory deficits caused by tooth loss in aged SAMP8 mice. (March 2021) - Kubo, Kin-ya; Ogasawara, Akifumi; Tsugane, Hiroko; Iinuma, Mitsuo; Takahashi, Toru; Azuma, Kagaku
Highlights: Tooth loss leads to spatial memory impairment and hippocampal abnormalities. An enriched environment improves hippocampus-related cognitive deficits. Tooth loss leads to myelin and synaptic abnormalities in the hippocampus. An enriched environment ameliorates structural abnormalities induced by tooth loss. Tooth loss induces deficits that can be attenuated by an enriched environment. Abstract: Objective: Prolonged mild stress due to tooth loss leads to morphologic and functional alterations of the hippocampus, as well as cognitive memory impairments in aged animals. An enriched environment improves stress-induced hippocampus-dependent cognitive impairments. The potential mechanisms underlying the beneficial effects of an enriched environment, however, remain unclear. In the present study, we investigated whether an enriched environment affects morphologic remodeling of the hippocampal myelin, synapses, and spatial learning deficits caused by tooth loss in aged senescence-accelerated mouse strain P8 (SAMP8) mice. Design: SAMP8 mice (8 months old) with either teeth intact or teeth extracted were raised in a standard or enriched environment for three weeks. Spatial learning and memory ability was evaluated in a Morris water maze test. The morphologic features of the myelin sheath and synapses in the hippocampus were investigated by electron microscopy. Results: Mice with tooth loss had a thinner myelin sheaths and shorter postsynaptic densities in the hippocampal CA1 region, and impaired hippocampus-dependent spatial learning ability. Exposure to an enriched environment ameliorated the hypomyelination and synaptic alterations, and spatial learning and memory impairments induced by tooth loss in aged SAMP8 mice. Conclusion: Our findings indicate that an enriched environment ameliorates hippocampal hypomyelination and synapse morphologic abnormalities, as well as learning deficits induced by tooth loss in aged SAMP8 mice.